Acute forced exercise increases Bdnf IV mRNA and reduces exploratory behavior in C57BL/6J mice. (5th November 2019) - Venezia, Andrew C.; Hyer, Molly M.; Glasper, Erica R.; Roth, Stephen M.; Quinlan, Elizabeth M.
Abstract: Acute exercise has been shown to improve memory in humans. Potential mechanisms include increased Bdnf expression, noradrenergic activity and modification of glutamate receptors. Because mice are commonly used to study exercise and brain plasticity, it is important to explore how acute exercise impacts behavior in this model. C57BL/6J mice were assigned to three groups: control, moderate‐intensity running, and high‐intensity running. Control mice were placed on a stationary treadmill for 30 minutes and moderate‐ and high‐intensity mice ran for 30 minutes at 12 and 15‐17 m/min, respectively. Mice were sacrificed immediately after running and the hippocampus removed. Total Bdnf, Bdnf exon IV, and glutamate receptor subunits were quantified with quantitative polymerase chain reaction. Total and phosphorylated GluR1 (Ser845 and Ser831) protein was quantified following immunoblotting. Utilizing the same protocol for control and high‐intensity running, object location memory was examined in a separate cohort of mice. Anxiety‐like behavior was assessed in the open field task (OFT) in a third cohort of mice that were separated into four groups: control‐saline, control‐DSP‐4, acute exercise‐saline, and acute exercise‐DSP‐4. DSP‐4 was used to lesion the central noradrenergic system. We observed higher Bdnf IV mRNA in high‐intensity runners compared to controls, but no effects of acute exercise on memory. In the OFT, runners traveled less distance and spent more time grooming than controls. DSP‐4 did not attenuate the effects of exercise. A single bout of exercise increases Bdnf IV mRNA in an intensity‐dependent manner; however, high‐intensity running reduces exploratory behavior in C57BL/6J mice. Abstract : A single acute bout of high‐intensity exercise reduces exploratory behavior and increases time spent self‐grooming.